The Role of TPQ Al-Ikhlas Teachers in Improving the Ability to Read and Write Al-Qur'an Santri in Longa Village - Salwi; Nur Rahmah Al Haqq; Mahariani (IAIN KENDARI, 2025)
Islamic character building in the work environment is an important element in creating an organizational culture with integrity, ethics, and productivity. The theories used as a foundation in this study include the theory of character education and Islamic education values. Then this study aims to analyze the Islamic education approach in building Islamic character in Ruangguru employees, a leading education technology company in Indonesia. This approach involves applying Islamic values such as honesty, responsibility, hard work, and caring through training programs, mentoring, and a work culture that supports spiritual learning. This research uses a qualitative method with data collection through in- depth interviews, observation, and documentation studies. The results show that Islamic character building not only improves individual employee morality but also strengthens team cohesion and overall company performance. By consistently applying Islamic values, Ruangguru is able to become a model organization that is oriented towards success in this world and the hereafter.